TEACHING ENGLISH EXPERIENCE IN KAMPUS MENGAJAR (KM) PROGRAM: A DESCRIPTIVE QUALITATIVE STUDY ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Ramadhani, Aisyah Anastazia; Saiful; Mahmudah, Dzur Rif'ah (Journal of Language Testing and Assessment, 2024)
This study aims to find out challenges that faced by English Education Department Students at Universitas Muhammadiyah Makassar when teaching English in the Kampus Mengajar (KM) program and strategies that English Education Department Students used to overcome the challenges that arise. This study is descriptive qualitative method and uses interview as an instruments to collect data. In which the number of subjects in this study were six of English Education Department Students who participated in the Kampus Mengajar (KM) program. The results of the study indicate there were several challenges faced by English Education Department students when teaching English in the Kampus Mengajar (KM) program, namely pronunciation problems, students lack knowledge about English, students’ lack of enthusiasm and limited school’s facilities. Meanwhile the strategies were used by English Education Department students to overcome the challenges that arise, namely repeating lessons, using pictures and also using games